The Systemic Inflammatory Response and Its Relationship to Pain and Other Symptoms in Advanced Cancer. (21st August 2013) - Laird, Barry J.; McMillan, Donald C.; Fayers, Peter; Fearon, Kenneth; Kaasa, Stein; Fallon, Marie T.; Klepstad, Pål
Abstract : Introduction: Inflammation has been identified as a hallmark of cancer and may be necessary for tumorgenesis and maintenance of the cancer state. Inflammation‐related symptoms are common in those with cancer; however, little is known about the relationship between symptoms and systemic inflammation in cancer. The aim of the present study was to examine the relationship between symptoms and systemic inflammation in a large cohort of patients with advanced cancer. Methods: Data from an international cohort of patients with advanced cancer were analyzed. Symptoms and patient‐related outcomes were recorded using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire—Core Questionnaire. Systemic inflammation was assessed using C‐reactive protein levels. The relationship between these symptoms and systemic inflammation was examined using Spearman rank correlation (ρ) and the Mann‐Whitney U test. Results: Data were available for 1, 466 patients across eight European countries; 1, 215 patients (83%) had metastatic disease at study entry. The median survival was 3.8 months (interquartile range [IQR] 1.3–12.2 months). The following were associated with increased levels of inflammation: performance status (ρ = .179), survival (ρ = .347), pain (ρ = .154), anorexia (ρ = .206), cognitive dysfunction (ρ = .137), dyspnea ( p = .150), fatigue (ρ = .197), physical dysfunction (ρ = .207), role dysfunction (ρ = .176), social dysfunction (ρ = .132), and poor quality of life (ρ = .178). All were statistically significant at p < .001. Conclusion: The results show that the majority of cancer symptoms are associated with inflammation. The strength of the potential relationship between systemic inflammation and common cancer symptoms should be examined further within the context of an anti‐inflammatory intervention trial. Abstract : Inflammation has been identified as a hallmark of cancer, and inflammation‐related symptoms are common in those with cancer. This study examined the relationship between symptoms and systemic inflammation in a large multinational cohort of patients with advanced cancer and found that the majority of cancer symptoms are associated with inflammation.